THE EFFECT OF PROBLEM-BASED LEARNING MODEL ON THE IMPROVEMENT OF STUDENTS’ CRITICAL THINKING AND LEARNING OUTCOMES IN SOCIAL SCIENCE LEARNING SUBJECT IN CLASS 5A OF SD KRISTEN 03 EBEN HAEZER SALATIGA - Andi Setyawan; Krisma Widi Wardani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The classroom action research in this paper aims to increase students’ critical thinking and learning outcomes in Social Science learning subjects in Grade 5A of SD Kristen 3 Eben Haezer Salatiga in the second semester of the academic year 2022/2023 by implementing the Problem-Based Learning (PBL) model. The research findings reveal that the application of PBL had a significant positive impact. The student’s critical thinking skills indicate improvement with the students’ percentage in the high and very high categories increasing from 30% to 62% in cycle 1, and achieving 81% in cycle 2. Moreover, the implementation of PBL successfully increased the percentage of students who achieved learning achievement from 26.92% to 92.31%. There was also an improvement in the average student scores from 55 to 84.29 in cycle 2. The steps of the PBL model applied in the research of this paper included orienting students to the problem, organizing students to conduct research, guiding independent or group investigations, developing and presenting work results, as well as analyzing and evaluating problem-solving processes. Thus, it can be concluded that the PBL model is effective in increasing students’ critical thinking and learning outcomes in the Social Science learning subject in Grade 5A of SD Kristen 3 Eben Haezer Salatiga. The implication of the research is that the PBL model can be utilized as an effective alternative toimprove student’s critical thinking and learning outcomes in Social Science learning.